Optimizing viral load suppression in Kenyan children on antiretroviral therapy (Opt4Kids) - Rena C. Patel; Patrick Oyaro; Beryne Odeny; Irene Mukui; Katherine K. Thomas; Monisha Sharma; James Wagude; Eunice Kinywa; Frederick Oluoch; Francesca Odhiambo; Boaz Oyaro; Grace C. John-Stewart; et al. (Contemporary Clinical Trials Communications, 2020)
Background: As many as 40% of the 1 million children living with HIV (CLHIV) receiving antiretroviral treatment (ART) in resource limited settings have not achieved viral suppression (VS). Kenya has a large burden of pediatric HIV with nearly 140,000 CLHIV. Feasible, scalable, and cost-effective approaches to ensure VS in CLHIV are urgently needed. The goal of this study is to determine the feasibility and impact of point-of-care (POC) viral load (VL) and targeted drug resistance mutation (DRM) testing to improve VS in children on ART in Kenya. Methods: We are conducting a randomized controlled study to evaluate the use of POC VL and targeted DRM testing among 704 children aged 1–14 years on ART at health facilities in western Kenya. Children are randomized 1:1 to intervention (higher frequency POC VL and targeted DRM testing) vs. control (standard-of-care) arms and followed for 12 months. Our primary outcome is VS (VL < 1000 copies/mL) 12 months after enrollment by study arm. Secondary outcomes include time to VS and the impact of targeted DRM testing on VS. In addition, key informant interviews with patients and providers will generate an understanding of how the POC VL intervention functions. Finally, we will model the cost-effectiveness of POC VL combined with targeted DRM testing. Discussion: This study will provide critical information on the impact of POC VL and DRM testing on VS among CLHIV on ART in a resource-limited setting and directly address the need to find approaches that maximize VS among children on ART. Trials registration: NCT03820323.